2002
DOI: 10.1034/j.1399-3054.2002.1150401.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of Antarctic vascular plants

Abstract: Most of the ice and snow-free land in the Antarctic summer is found along the Antarctic Peninsula and adjacent islands and coastal areas of the continent. This is the area where most of the Antarctic vegetation is found. Mean air temperature tends to be above zero during the summer in parts of the Maritime Antarctic. The most commonly found photosynthetic organisms in the Maritime Antarctic and continental edge are lichens (around 380 species) and bryophytes (130 species). Only two vascular plants, Deschampsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
128
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 46 publications
1
128
0
9
Order By: Relevance
“…The studies by Zúñiga et al (1994Zúñiga et al ( , 1996 that of other grasses while the soluble carbohydrates level is higher than in cereals. Alberdi et al (2002) suggested that carbohydrate accumulation could be related to enhanced freezing tolerance of this species. Our observations support this hypothesis and it seems even more true for Colobanthus quitensis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The studies by Zúñiga et al (1994Zúñiga et al ( , 1996 that of other grasses while the soluble carbohydrates level is higher than in cereals. Alberdi et al (2002) suggested that carbohydrate accumulation could be related to enhanced freezing tolerance of this species. Our observations support this hypothesis and it seems even more true for Colobanthus quitensis.…”
Section: Discussionmentioning
confidence: 96%
“…Plants have to be able to cope with severe abiotic stresses, caused by low temperature, repeated freezing and thawing, repeated desiccation, high irradiance and salinity (Alberdi et al 2002). The acquisition of abiotic stress resistance by plants and seeds depends on chemical substances preventing adverse effects stress.…”
Section: Introductionmentioning
confidence: 99%
“…In Antarctica, snow cover is an important microclimatic factor in protecting plants from windblown ice and sand particles (Alberdi et al 2002). During the growing season, without the snow cover in ice-free areas, the moss populations are suitable to windblown ice and sand particles, causing damages in the leaves and consequently, reducing the photosynthesis area.…”
Section: Discussionmentioning
confidence: 99%
“…Microclimate, including factors such as ground-level wind speed, water availability, and low temperature, has a major influence on Antarctic plants growth (Alberdi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bartl.) that are probably most sensitive to warming, as well as of different mosses and macroalgae [4][5][6]. For using plant communities as indicators of cli matic changes it is essential to study the variability of their composition, as well as the parameters of plant edificators in relation to the ecological con ditions of their habitats.…”
mentioning
confidence: 99%